1998
DOI: 10.1038/sj.cdd.4400320
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant death in dark chondrocytes of the avian growth plate

Abstract: Growth plate chondrocytes of embryonic chick femurs were examined by electron microscopy, cytophotometry and autoradiography. Apart from the well-described`light' chondrocyte, a different`dark' type of chondrocyte was present, comprising 10 ± 35% of the cell population. They were found at all stages of chondrocyte differentiation and in all ages of the femurs studied. Well developed rough endoplasmatic reticulum and Golgi complex, many secretory vesicles, energetically active mitochondria and a lot of glycogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 26 publications
4
35
1
Order By: Relevance
“…Many of the chondrocytes had the appearance previously described as 'dark' [6]. These dark cells exhibited condensed chromatin, abundant endoplasmic reticulum (ER) and dark cytoplasm.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many of the chondrocytes had the appearance previously described as 'dark' [6]. These dark cells exhibited condensed chromatin, abundant endoplasmic reticulum (ER) and dark cytoplasm.…”
Section: Discussionmentioning
confidence: 93%
“…Experimental fracture studies have concluded that endochondral ossification plays a role in bone remodelling and that this process involves removal of chondrocytes via apoptosis [6,15]. The study presented here uses a rabbit fracture model to investigate cell death in the soft callus and to localise deadldying chondrocytes in relation to their surrounding matrix at different time points during the fracture healing process.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that their nuclear membrane often contains defects. The segments ravel into small inverted buds and dissolve together with adjacent chromatic clumps to release pore complexes [4,18,33,38].…”
Section: Dark Chondrocytesmentioning
confidence: 99%
“…These cells were unable to live or die analogous to a paralytic state, a form of cell death similar to dark chondrocytes (see below). These cells underwent autophagy [38,39] that is a process that involves the cell using its own components to degrade itself by lysosomes. These cells contain double-membrane autophagic vacuoles, termed autophagosomes that are used for self degradation.…”
Section: Authophagal Bodiesmentioning
confidence: 99%
“…Indeed, the complexity of the chondro-osseous (cartilage and bone) junction has been the cause of considerable debate, especially the morphological appearance of the terminal chondrocyte. For example, Roach and co-workers 5,6 have described cells that exhibited unusual ultramicroscopic features. It was suggested that these cells were in "limbo", unable to live or die.…”
Section: Introductionmentioning
confidence: 99%